Ready for IELTS : - McCarter, Sam (Macmillan, 2010)
Ready for IELTS is a comprehensive course which offers thorough preparation for the IELTS Academic exam. All four parts of the exam are systematically developed and practiced in each unit, while in-depth exam training is given in the form of regular help boxes. This step-by-step approach ensures that students will be fully prepared and confident when taking the IELTS Academic exam.